EFFICIENCY OF INFILTRATIVE ARTICAINE V/S NERVE BLOCK LIDOCAINE IN MANDIBULAR THIRD MOLARS SURGERY - Baeza, Solange; Rojo, Felipe; Bialostocki, Ebner (Applied Sciences in Dentistry, 2020)
Objective: To compare the efficiency of infiltrative articaine versus nerve block lidocaine in pain management during mandibular third molar extraction. Material and methods: Randomized clinical trial. 25 patients with symmetrical semi-included third molars were analyzed, to which infiltrative Articaine and Nerve block Lidocaine were randomly applied to each demi-side. The proposed variable was the efficiency of the anesthesia protocol. Results were analyzed with a proportional comparison Z test, analyzed with a confidence level of 95%. Results: The infiltrative articaine efficiency was 92% for B-group, existing no statistically significant difference to Nerve block lidocaine (p<0.05). Conclusion: Infiltrative articaine achieves pain management comparable to that of nerve block lidocaine.